(untitled) (Biological Sciences - PJSIR, 1995)
Noise study was conducted in the Filament Take-up Hall, Texturizing Hall and Compressor House of a Synthetic Fibre Plant to assess the level and quality of noise, occupational noise exposure and speech interference levels in these units. The Filament Take-up Hall is fitted with 40 high speed winding machines on a vertical stand and the Texturizing Hall is fitted with 9 texturizing machines. The Compressor House is fitted with appropriate machines, with door and windows open.